The Role of Restaurant Taxes in Increasing Medan City’s Original Revenue - Alhusna, Syifa; Harahap , Rahmat Daim (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Restaurant Tax is a tax on the services provided by the restaurant. A restaurant is a facility that provides food and/or beverages with a fee, which includes restaurants, cafeterias, canteens, stalls, bars, and the like. This study aims to determine the role of restaurant tax in increasing the original income of the Medan City area. The data used is qualitative. This research uses descriptive qualitative research methods. Based on the results of the study, the role of Restaurant Tax is quite influential as a source of regional taxes which is an element in PAD as a support for the implementation of national development.